Measuring Abdominal Circumference and Skeletal Muscle From a Single Cross‐Sectional Computed Tomography Image: A Step‐by‐Step Guide for Clinicians Using National Institutes of Health ImageJ. (21st September 2015) - Gomez‐Perez, Sandra L.; Haus, Jacob M.; Sheean, Patricia; Patel, Bimal; Mar, Winnie; Chaudhry, Vivek; McKeever, Liam; Braunschweig, Carol
Abstract : Diagnostic computed tomography (CT) scans provide numerous opportunities for body composition analysis, including quantification of abdominal circumference, abdominal adipose tissues (subcutaneous, visceral, and intermuscular), and skeletal muscle (SM). CT scans are commonly performed for diagnostic purposes in clinical settings, and methods for estimating abdominal circumference and whole‐body SM mass from them have been reported. A supine abdominal circumference is a valid measure of waist circumference (WC). The valid correlation between a single cross‐sectional CT image (slice) at third lumbar (L3) for abdominal SM and whole‐body SM is also well established. Sarcopenia refers to the age‐associated decreased in muscle mass and function. A single dimensional definition of sarcopenia using CT images that includes only assessment of low whole‐body SM has been validated in clinical populations and significantly associated with negative outcomes. However, despite the availability and precision of SM data from CT scans and the relationship between these measurements and clinical outcomes, they have not become a routine component of clinical nutrition assessment. Lack of time, training, and expense are potential barriers that prevent clinicians from fully embracing this technique. This tutorial presents a systematic, step‐by‐step guide to quickly quantify abdominal circumference as a proxy for WC and SM using a cross‐sectional CT image from a regional diagnostic CT scan for clinical identification of sarcopenia. Multiple software options are available, but this tutorial uses ImageJ, a free public‐domain software developed by the National Institutes of Health.